Religion, rulers, and conflict - YILDIRIM, SADULLAH (My University, 2023)
We offer new data and a new analytical approach to examine the roots of today’s civil conflicts that lie deeply in religious and political history. Religion’s effect on today’s conflicts come not from contemporary fractionalization or polarization, but from the deep-rooted effects of historical fragmentation coupled with rulers who could manipulate divisions by favoring co-religionists. To test the resulting hypotheses, we use a new dataset that includes annual information regarding the religious and political histories of today’s societies since the year 1000. We run regression analysis at both country and ethnic group levels. The results show that the likelihood of contemporary new conflicts is higher in societies that historically experienced religious fragmentation with rulers who shared religion with one of the groups and could thus favor coreligionists over others. Economic inequality and political grievances served as channels of transmission.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Social Sciences & Humanities; Conflict; Discrimination; Favoritism; Grievance; Historical roots; Inequality; Religion